Novice general education teachers' perceptions of preparedness in U.S. public schools: The impact of learning about and working with multilingual students. (August 2022) - Kiramba, Lydiah Kananu; Deng, Qizhen; Viesca, Kara
Abstract: This study examined perceptions of preparedness among novice general education teachers using 2015/16 National Teacher and Principal Survey data. Results show that teachers with training in teaching multilingual learners reported higher perceived preparedness than those without across all five general aspects of teaching (i.e., instructional methods, teaching subject matters, assessing students, differentiating instruction, and using assessment data to inform instruction). Further, teacher preparedness in differentiating instruction was positively associated with the percentage of multilingual learners in a teacher's classroom. Findings suggest that learning to teach multilingual learners supports novice general content teachers to feel more prepared as teachers overall. Highlights: Examines perceptions of preparedness among novice general education teachers using 2015/16 National Survey data. Predictor of overall perceptions of preparedness is pre-service coursework on teaching multilingual students. The % of multilingual learners in classrooms is linked to teachers' overall perceptions of preparedness. Learning opportunities that prepare teachers for multilingual learners appear to support overall preparedness for teaching. Teacher preparation should include course(s) and practicum(s) on teaching multilingual learners for all teachers.